Dietary Bacillus subtilis benefits meat quality by regulating the muscle fiber type and antioxidant capacity of broilers - Hairong Wang; Chuanpi Xiao; Jiqiang Li; Rongrong Liang; Yunge Liu; Zhigang Song; Johan Buyse; Lixian Zhu (Poultry Science)
ABSTRACT: The effects of dietary Bacillus subtilis (BS) on the meat quality of broilers were evaluated, with an emphasis on the regulation of muscle fiber types and antioxidant capabilities. One hundred and forty-four Arbor Acres male broilers were divided into 3 treatment groups (0, 300 mg/kg and 500 mg/kg dietary BS) and raised for 35 d. The results suggested that BS improved meat quality by improving the muscular pH, meat color, water holding capacity and shear force. Immunofluorescence staining revealed a positive impact of BS on the muscle fiber transformation in thigh muscles, and the gene/protein expression data from specific muscle fiber types confirmed this finding. BS activated AMP-activated protein kinase (AMPK), silent information regulator 1 and peroxisome proliferator-activated receptor gamma coactivator 1alpha. The postmortem analysis revealed that BS increased the activity of glutathione peroxidase and total antioxidant capacity while decreasing the malondialdehyde content. Additionally, BS increased the gene and protein expression of nuclear factor-like 2 (Nrf2) and activated the Nrf2 signaling pathway, including its downstream factors, such as heme oxygenase-1, catalase, superoxide dismutase and glutathione peroxidase. In conclusion, dietary BS improved meat quality by modifying muscle fiber types and enhancing the antioxidant capacity in broilers.